Estimation of Polymer-Solvent Interaction Parameter K' For Polyproplylene in Cyclohexane - Husain, M.M.; Islam, M.I.; Kumar, Raj (Asian Journal of Chemistry, 2010)
In the present work, the estimation of polymer-solvent interaction parameter K´ for polypropylene in cyclohexane has been done.